A COMPARATIVE STRUCTURAL-SEMANTIC ANALYSIS OF COMPLEX (SUBORDINATE) SENTENCES IN UZBEK AND ENGLISH: TYPES OF SUBORDINATE CLAUSES, LINKING DEVICES, AND COMPONENT ORDER (Eureka Journal of Language, Culture & Social Change, 2026)
This study presents a comparative structural-semantic analysis of complex sentences with subordination in Uzbek and English, focusing on three interconnected parameters: the typology of subordinate clauses, the linguistic devices that establish clause linkage, and the ordering principles that shape component distribution in discourse. Although both languages employ subordination to encode logical relations such as cause, condition, purpose, time, and concession, they differ substantially in how these relations are grammaticalized. The analysis examines how English predominantly relies on finite subordinate clauses introduced by conjunctions and relative markers, while Uzbek shows a strong preference for non-finite predicative forms, converbs, and nominalized clause-like structures that function as syntactic dependents. Particular attention is given to the mapping between semantic relations and formal exponents, including the functional range of subordinators, correlatives, and morphosyntactic markers of dependency. The study also addresses component order as an interpretive factor, comparing the relatively flexible but information-structure-sensitive placement of subordinate clauses in English with the head-final tendencies and clause-chaining patterns characteristic of Uzbek. By integrating structural description with semantic classification and distributional evidence from contemporary written and academic registers, the research clarifies how comparable meanings can be realized through different grammatical strategies. The findings aim to support contrastive linguistics, translation studies, and advanced grammar pedagogy in EFL and Uzbek philological contexts, offering an empirically grounded account of subordination that prioritizes functional equivalence and intelligibility across typological boundaries.
Keywords: Complex sentence, subordination, subordinate clause types, linking devices, clause order, contrastive syntax, Uzbek syntax, English syntax, structural-semantic analysis, information structure